KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MIN RUKOH BANDA ACEH - Elda Safitri; Yusrizal .; Djailani AR (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: Success or failure of education and learning in school is influenced by the ability of principals to manage every component of the school. In his capacity as the leader of the principal obligation to improve the performance of teachers, especially in implementing an effective learning process. The purpose of this study to determine: the principal's managerial ability in the preparation of the teacher's performance improvement program, the managerial ability of the principal in the implementation of the program to improve teacher performance, and barriers encountered principals in improving teacher performance in MIN Rukoh Banda Aceh. The study used descriptive qualitative approach. Data was collected through observation, interviews, and documentation. Subjects were principals and teachers. The results showed that; 1) Preparation of a teacher's performance improvement program carried out at the end of each school year that include intra and extra-curricular activities, school facilities and infrastructure improvements, preparing administrative / learning tool by teachers and others as deemed necessary, including the need for the funds necessary to support learning activities teaching; 2) In the exercise program to improve teacher performance principals apply democratic leadership style. Facing the teachers are usually the principal the principal exchange ideas with teachers so finding an effective way to improve teacher kinetrja teachers in the development of the learning process; and 3) the principal obstacle encountered in improving the performance of teachers, among others, the lack of availability of funds for teacher training outside office hours, there is still a small proportion of teachers are not active and have not been able to induce the result of upgrading to his friend. A small percentage of teachers who have not been able to in the mastery of the foundation of education, so that the impact on performance in implementing the learning.Keywords: Managerial Principal and Teacher PerformanceAbstrak: Sukses tidaknya pendidikan dan pembelajaran di sekolah sangat dipengaruhi oleh kemampuan kepala sekolah dalam mengelola setiap komponen sekolah. Dalam kapasitasnya sebagai pemimpin kepala sekolah berkewajiban untuk meningkatkan kinerja guru khususnya dalam melaksanakan proses pembelajaran yang efektif. Tujuan penelitian ini untuk mengetahui: kemampuan manajerial kepala sekolah dalam penyusunan program peningkatan kinerja guru, kemampuan manajerial kepala sekolah dalam pelaksanaan program peningkatan kinerja guru, dan hambatan-hambatan yang ditemui kepala sekolah dalam peningkatan kinerja guru pada MIN Rukoh Banda Aceh. Penelitian menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik  pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi. Subjek penelitian adalah kepala sekolah dan guru-guru. Hasil  penelitian  menunjukkan bahwa; 1) Penyusunan program peningkatan kinerja guru dilakukan pada setiap akhir tahun pelajaran yang meliputi kegiatan intra dan ekstrakurikuler, perbaikan sarana dan prasarana sekolah, menyusun administrasi/perangkat pembelajaran oleh guru dan lain-lain yang dianggap perlu, termasuk kebutuhan dana yang diperlukan untuk menunjang kegiatan belajar mengajar;  2) Dalam pelaksanaan program peningkatan kinerja guru kepala sekolah menerapkan gaya kepemimpinan demokratis. Menghadapi guru-guru biasanya kepala sekolah kepala sekolah bertukar pikiran dengan guru-guru sehingga menemukan satu cara efektif  untuk meningkatkan kinetrja guru guru dalam pengembangan proses pembelajaran; dan 3) Hambatan yang ditemui kepala sekolah dalam meningkatkan kinerja guru antara lain kurangnya tersedianya dana untuk pelatihan guru di luar jam dinas, masih ada sebagian kecil guru tidak aktif dan hasil penataran belum mampu mengimbas kepada temannya. Sebagian kecil guru yang belum mampu dalam penguasaan landasan kependidikan, sehingga berdampak terhadap kinerjanya dalam melaksanakan pembelajaran.Kata kunci: Manajerial Kepala Sekolah dan Kinerja Guru